2017
DOI: 10.1007/s00004-017-0334-z
|View full text |Cite
|
Sign up to set email alerts
|

A Co-Evolution Model of Planning Space and Self-Built Space for Compact Settlements in Rural China

Abstract: The process of compact development of rural settlements in the North China Plain is influenced by centralised control of planning spaces and a deficiency of self-built spaces, thereby resulting in a crisis of spatial characteristics. This essay considers the mutually driving effects of top-down planning spaces and bottom-up self-built spaces as well as the corresponding dynamic mechanisms of unified construction and self-help construction formed in spatial system evolution. The goal is to explore a method appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…A novel approach for estimating floor spaces was presented in [58], a space recognition algorithm for building spaces was used for performance simulations [59], a spatial analysis linked with radiation effects was performed in [60], a decision-making support method was presented using design-space exploration in [61] and information extraction was performed in [62]. Included in the research based on design are the application of BIM and related analyses such as parking space allocation [63], climate daylight simulation [64], building adaptation design using physics-based simulation tools, building design sensitivity analyses [65], graphical visualization assists analyses and flow around buildings and indoor environments including turbulence [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Building Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel approach for estimating floor spaces was presented in [58], a space recognition algorithm for building spaces was used for performance simulations [59], a spatial analysis linked with radiation effects was performed in [60], a decision-making support method was presented using design-space exploration in [61] and information extraction was performed in [62]. Included in the research based on design are the application of BIM and related analyses such as parking space allocation [63], climate daylight simulation [64], building adaptation design using physics-based simulation tools, building design sensitivity analyses [65], graphical visualization assists analyses and flow around buildings and indoor environments including turbulence [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Building Designmentioning
confidence: 99%
“…Studies relating to the adoption of new and upcoming technologies were found that are in line with significant topics such as sustainability. Inclusion of BIM for the purposes of planning ahead for potential conflict detection has been studied, where an additional dimension, i.e., time, was added to the simulation [74]. The significant advantage of BIM being digital is beneficial for performing numerical calculations for planning a purpose for a space given a specific condition [75,76].…”
Section: Urban Planningmentioning
confidence: 99%
“…Since 1990, there has been an increasing number of studies on the villages in China, covering such aspects as the village space and form, village division and pedigree, village evolution, village protection and development, ancient village renovation, new village construction, etc. Researchers not only focus on the traditional residential buildings, but they also carry out research on the overall village spaces [1][2][3][4][5][6]. In recent years, under the influence of the topology, anthropology, sociology, and ecology theories, researchers have adopted new research methods in the domestic research on villages, such as geographic information system (GIS) and spatial syntax analyses, to conduct quantitative research on the spatial forms of villages.…”
Section: Introductionmentioning
confidence: 99%
“…Generative design (lat. generatum -"generate, produce") is found as one of the strategic directions, that represent the design process as the result of exclusively mathematical calculations generated by the CAD system (computer-aided design) [8,9], which has been already applied for the optimization of the systems geometry [10,11] and spatial planning issues [12,13].…”
Section: Introductionmentioning
confidence: 99%